Robinson crusoe: read it yourself (ladybird) - Hunia, Fran; Ayton, Robert Defoe, Daniel (Ladybird Loughborough, 1993)
Experiences of an Englishman stranded by shipwreck on a desert island, where he survives for time thirty years